2013
DOI: 10.1111/pai.12043
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis in children: which factors are relevant? (review of the literature)

Abstract: Allergic Contact Dermatitis (ACD) in children is increasing. Sensitization to contact allergens can start in early infancy. The epidermal barrier is crucial for the development of sensitization and elicitation of ACD. Factors that may influence the onset of sensitization in children are atopic dermatitis, skin barrier defects and intense or repetitive contact with allergens. Topical treatment of ACD is associated with cutaneous sensitization, although the prevalence is not high. ACD because of haptens in shoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 111 publications
(156 reference statements)
7
39
1
1
Order By: Relevance
“…As regards the prevalence of at least a positive reaction to a hapten of the EBS, in our study population, we found virtually no difference between children with AD and children without. This finding is in accordance with other studies . Nickel sensitization is often caused by piercing, which bypasses the epidermal barrier presumably impaired in AD.…”
Section: Discussionsupporting
confidence: 93%
“…As regards the prevalence of at least a positive reaction to a hapten of the EBS, in our study population, we found virtually no difference between children with AD and children without. This finding is in accordance with other studies . Nickel sensitization is often caused by piercing, which bypasses the epidermal barrier presumably impaired in AD.…”
Section: Discussionsupporting
confidence: 93%
“…19 Women are more likely to be diagnosed with contact dermatitis than men. [19][20][21] Allergic contact dermatitis is not uncommon in children and is on the rise. 22 Having atopic eczema, increases the risk of irritant contact dermatitis because of impaired skin barrier function.…”
Section: Who Gets Contact Dermatitis?mentioning
confidence: 99%
“…Impaired skin barrier function has been a suspected risk factor but results of studies have been conflicting and risk may be allergen-specific [17,18,19,20]. Recognition of CD in the setting of coexisting skin disease requires a high index of suspicion based on personal/family history, presence of xerosis, and, if necessary, results of “patch testing” (although the sensitivity of patch testing is less than 70%).…”
Section: Inflammatory Skin Conditionsmentioning
confidence: 99%